Mobe leaf (Artocarpus lakoocha Buch. Ham) ethanol extract's antibacterial activity on Streptococcus mutans cell membrane leakage and biofilm formation: An in vitro study - Bahirrah, Siti; Satria, Denny; Yuwanda, Cindy (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Using fixed orthodontic appliances inhibits oral hygiene, which can lead to the increased development of biofilms and Streptococcus mutans, a cariogenic bacterium that is well known for causing dental caries, derived from bacteria of the Streptococcus genus. In order to decrease biofilm and the degree of cariogenic bacteria in the oral cavity, a variety of herbal ingredients are used. Among these, mobe (Artocarpus lakoocha Buch. Ham) leaves are herbal ingredients with antibacterial properties. Purpose: This study aimed to investigate the antibacterial activity, antibiofilm, and leakage of DNA and protein from mobe leaves. Methods: The diffusion method was used to assess antibacterial activity and determine the minimum inhibitory concentration. The antibiofilm activity was evaluated with Ultraviolet–visible (UV-Vis) spectrophotometry (600 nm), using violet crystal staining. The detection of DNA and protein leakage was carried out by checking for absorbance values using the UV-Vis spectrophotometry (260 nm and 280 nm). An increase in the absorbance value in the measured cell indicated an increase in the level of cell content produced by the cell. One-way analysis of variance was used statistically analyze the results of this study (P < 0.05). Results: Mobe leaf (A. lakoocha) extract's minimum inhibitory concentration level was 3.125 mg/ml, the effective concentration of ethanol extract for inhibiting biofilm formation was 3.125 mg/ml, and the effective concentration of ethanol extract that could cause DNA and protein leakage was 50 mg/ml. Conclusions: Mobe leaf extract has good MIC for S. mutans.